Assessment of spatial nutrient variability at farm level for castor crop (Ricinus communis l.) in semiarid region of Telangana state in India: Assessment of spatial nutrient variability at farm level for castor crop (Ricinus communis l.) in semiarid region of Telangana state in India - M SHANKARAIAH; P SURENDRA BABU; M CHANDINI PATNAIK; P SONIYA (Journal of Oilseeds Research, 2023)
Site Specific Nutrient Management is a system for maximum yields in field crops. Nutrient Management Zones were developed for castor crop (Ricinus communis L.) in Inceptisols. Grids of 15 x 15 m were made in one hectare and soil samples were collected from each grid and were analyzed for soil characteristics and all available nutrients. Based on analytical data the geo-statistical analysis, varoni maps and different models were developed. The castor yield data was compared in nutrient management zones with farmers practice (FP) and recommended dose of fertilizers (RDF). The variable rates of fertilizers used in SSNM was 92, 53, 15, 40 & 25 kg of N, P, K, S and Zn/ ha and 100, 40, 30 and 80, 40, 30 kg of N, P, K in farmers practice and RDF plots and the yields realized were 28 q/ha and 15 and 13 q/ha in SSNM, RDF and farmer’s practice treatments respectively.